1984
DOI: 10.1111/j.1365-2265.1984.tb03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ‘Physiological’ Doses of Triiodothyronine Replacement on the Hormonal and Metabolic Adaptation to Short‐term Semistarvation and to Low‐calorie Diet in Obese Patients

Abstract: In four groups of obese patients matched for Body Mass Index (BMI), we studied the effects of different 3-week semi-starvation treatments followed by an 8-week hypocaloric (1008 kcal, protein 20%, carbohydrate 40%) diet with or without low doses of T3 therapy. Dietary intake (formula diet) in the semi-starvation period was 480 kcal, with 66 g protein (P) and 51 g carbohydrate (CHO) in groups I and III and with 33 g P and 84 g CHO in groups II and IV. Moreover, groups III and IV were given low doses (20 microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…This would point to differences in kidney metabolism as a potential causative factor, and since the volunteers abstained from physical exercise during experiment B, this may have influenced the observation. In another study, starvation and altered protein energy intake was shown not to affect alanine excretion in obese patients treated with triiodothyronine (Pasquali et al 1984), indicating that even major dietary changes are not likely to explain the observed changes. A larger study would be necessary to elucidate a possible effect of exercise or other factors on alanine excretion.…”
Section: Diet Culturementioning
confidence: 96%
“…This would point to differences in kidney metabolism as a potential causative factor, and since the volunteers abstained from physical exercise during experiment B, this may have influenced the observation. In another study, starvation and altered protein energy intake was shown not to affect alanine excretion in obese patients treated with triiodothyronine (Pasquali et al 1984), indicating that even major dietary changes are not likely to explain the observed changes. A larger study would be necessary to elucidate a possible effect of exercise or other factors on alanine excretion.…”
Section: Diet Culturementioning
confidence: 96%
“…As far as ADRs were concerned, two individuals dropped out of the study due to nervousness and increased heart rate, and hyperglycemia was detected in one patient with a family history of diabetes; all other individuals developed tachycardia (+18 bpm), a mild elevation in systolic blood pressure (+9 mmHg), and a reduction in diastolic blood pressure (-13 mmHg) (147). A group of 6 similar randomized trials analyzed weight loss and other metabolic parameters in 60 obese individuals (17-68 years old; 40% females) who were given LT3 (25-225 mcg/day) in combination with caloric restriction for 3 days to 12 weeks (148)(149)(150)(151)(152)(153). Treatment with LT3 accelerated weight loss, which was associated with a rise in urinary nitrogen, an indication that lean body mass was being lost.…”
Section: Clinical Trials In Which Liothyronine Therapy Was Used In Euthyroid Individualsmentioning
confidence: 99%
“…Doses of T3 varying between 5 and 20 mgaday have been reported to ameliorate hyperlipidemia, prevent hypoglycemia during VLCD, in¯uence concentration of SHBG and improve hormonal pro®le without major infIuence on either body weight or BMR 18 (although 5% increase of RER, 16 as well as a small but signi®cant decrease of BMI 17 is reported by some studies).…”
Section: ± 13mentioning
confidence: 99%